Highly Efficient and Stable Perovskite Solar Cells Enabled by Low‐Cost Industrial Organic Pigment Coating. (27th November 2020) - He, Qingquan; Worku, Michael; Liu, He; Lochner, Eric; Robb, Alex J.; Lteif, Sandrine; Vellore Winfred, J. S. Raaj; Hanson, Kenneth; Schlenoff, Joseph B.; Kim, Bumjoon J.; Ma, Biwu
Abstract: Surface passivation of perovskite solar cells (PSCs) using a low‐cost industrial organic pigment quinacridone (QA) is presented. The procedure involves solution processing a soluble derivative of QA, N, N ‐bis(tert‐butyloxycarbonyl)‐quinacridone (TBOC‐QA), followed by thermal annealing to convert TBOC‐QA into insoluble QA. With halide perovskite thin films coated by QA, PSCs based on methylammonium lead iodide (MAPbI3 ) showed significantly improved performance with remarkable stability. A PCE of 21.1 % was achieved, which is much higher than 18.9 % recorded for the unmodified devices. The QA coating with exceptional insolubility and hydrophobicity also led to greatly enhanced contact angle from 35.6° for the pristine MAPbI3 thin films to 77.2° for QA coated MAPbI3 thin films. The stability of QA passivated MAPbI3 perovskite thin films and PSCs were significantly enhanced, retaining about 90 % of the initial efficiencies after more than 1000 hours storage under ambient conditions. Abstract : A low‐cost industrial organic pigment, quinacridone (QA), was applied as surface passivation agent for perovskite solar cells (PSCs) by solution processing of a soluble QA derivative followed by thermal annealing to convert it into insoluble QA. Passivation with strong interactions between QA molecules and metal halides, together with the hydrophobicity of QA coating, enabled highly efficient PSCs with remarkable stability.